The Structural and Cultural Constraints on Policy Implementation : a case study on further education and training Colleges in South Africa - Jansen, Jonathan D. (University of Pretoria, 2013)
Thesis (PhD (Education Management and Policy Studies))--University of Pretoria, 2006.